Biomechanical interpretation of observed fatigue fractures of peripheral Nitinol stents in the superficial femoral arteries through in silico modelling. (September 2020) - Mazzaccaro, Daniela; Berti, Francesca; Antonini, Luca; Pennati, Giancarlo; Petrini, Lorenza; Migliavacca, Francesco; Nano, Giovanni
Abstract: Purpose: To suggest an in silico modelling approach to estimate the fatigue failure on peripheral Nitinol stents implanted in the superficial femoral artery (SFA) and interpret the clinically observed stent fractures of a retrospective series of patients. Materials and Methods: Preoperative data of 27 patients who underwent SFA Nitinol stenting were retrospectively analyzed. Data about preoperative features of the SFA and the lesion were collected. Follow-up data were also collected about the occurrence of restenosis/occlusion and stent fracture. Results: After a lengthening of the entire vessel, the occluded region was slightly stretched due to its high stiffness, whereas the healthy regions accommodated the artery length variation. The stent fatigue was predicted to be higher in the regions of low stiffness and higher shortening. In 7 out of 27 patients a stent fracture was clinically recorded. The model resulted to be accurate in 90% of the cases. Conclusions: The clinical outcomes in terms of biomechanical fatigue behavior of peripheral Nitinol stents of the SFA could be interpreted by our new approach.